Clinical manifestations, therapy and outcome of pandemic influenza a (H1N1) 2009 in hospitalized patients - Mikić Dragan; Nožić Darko; Kojić Miroslav; Popović Svetlana; Hristović Dejan; Rajić-Dimitrijević Radmila; Ćurčić Petar; Milanović Milomir; Glavatović Rade; Begović-Kuprešanin Vesna; Veljović Milić; Đorđević Dragan; et al. (Vojnosanitetski Pregled)
Background/Aim. Increasing number of epidemiological and clinical studies to date showed that the pandemic influenza A (H1N1) 2009, by its characteristics, significantly differs from infection caused by seasonal influenza. Therefore, the information about clinical spectrum of manifestations, risk factors for severe form of the disease, treatment and outcome in patients with novel flu are still collected. Methods. A total of 98 patients (mean age 32 ± 15 years, range 14-88 years) with the signs and symptoms of novel influenza were treated in the Clinic for Infectious and Tropical Diseases, Military Medical Academy. There were 74 (75.5%) patients with suspected influenza A (H1N1) 2009, 10 (10.2%) with the likelihood and 14 (14.3%) with the confirmed influenza. In all the patients we registered the basic demographic data, risk factors for severe disease, symptoms and signs of influenza, laboratory tests and chest radiography. We analyzed antiviral therapy use and disease outcome (survived, died). Results. The average time from the beginning of influenza A (H1N1) to the admission in hospital was 3 days (0-16 days) and from the moment of hospitalization to the Intensive Care Unit (ICU) admission was 2 days (0-5 days). There were 49 (50.0%) patients, 20-29 years of age and 5 (5.1%) patients older than 65. A total of 21 (21.4%) patients were with underlying disease, 18 (18.4%) were obese, 19 (19.4%) were cigarette smokers. All of the patients had fever, 81 (82.6%) cough, while dyspnea and diarrhea were registered in ¼ of the patients. In more than 75% of the patients laboratory tests were within normal limits. The realtime polymerase chain reaction (PCR) test for identification of influenza A (H1N1) 2009 was positive in 14 (77.8%), while pneumonia was verified in 30 (30.7%) of the patients. Six (6.1%) patients, mean age of 45 ± 14 years (31-59 years) were admitted to the ICU, of whom five (5.1%) had Adult Respiratory Distress Syndrome (ARDS). Risk factors were registered more frequently in the patients with acute respiratory failure (14.2% vs 4.9%, p < 0.05). A total of 67 (68.4%) patients received oseltamivir, 89 (90.1%) was applied to antibiotics and 64 (65.3%) were treated with a combined therapy. Antiviral therapy was applied to 43 (43.3%) patients in the first 48 hours from the onset of the disease, of whom only one (3.4%) developed ARDS. Fatal outcome was noted in 2.0% of the patients (2 of 98 patients) and in 33.3% of the patients treated in the ICU. Conclusion. Novel influenza A (H1N1) is most commonly manifested as a mild acute respiratory disease, which usually affects young healthy adults. A small number of the patients develop severe illness with acute respiratory failure and death. Patients seem to have benefit from antiviral therapy especially in first 48 hours.